Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - 1.5 - Complex Numbers - 1.5 Exercises - Page 120: 91


True. $(-i\sqrt 6)^4-(-i\sqrt 6)^2+14=56$

Work Step by Step

Let's test: $(-i\sqrt 6)^4-(-i\sqrt 6)^2+14=(-\sqrt 6i)^4-(-\sqrt 6i)^2+14=(-\sqrt 6)^4i^4-(-\sqrt 6)^2i^2+14=36(i^2)^2-6(-1)+14=36(-1)^2+6+14=36+6+14=56$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.